An Industrial systems design study on Goldwin Manufacturing Laboratory Corporation - Castillo, Corallie S.; Joson, Carlo Marx O.; Oberio, Erika R.; Rodriguez, Cherrylene S. (College of Engineering, 2001)
GOLDWIN MANUFACTURING LABORATORIES CORPORATION is a "toll" or contract manufacturer for cosmetic marketing firms, clinics, and traders who sell products bought from Goldwin labeled with their own brand name. The company offers skin care products. Goldwin produces skin care products that are segregated as follows: herbal soaps, special soaps, facial cleansers/creams, shampoos/lotions, and others. Their service to their customer does not end with these products since whenever a customer asks them to manufacture a certain skin care product, they would manufacture the needed product if they found out that they are capable of doing it. At present, roughly seventy (70%) of their manufacturing output is served for the local customers. The next thirty percent (30%) of the product produced is exported to several countries such as USA, Indonesia, Sultanate of Oman, South Korea, Malaysia, Canada, Thailand, etc. The group documented the company's system giving particular attention on the following organizations: purchasing, inventory management, stores/warehousing, manufacturing, finished goods warehousing operations, transport operations, and customer service operations. The purchasing strategies employed by the company are: multiple sourcing and supplier agreements. Multiple sourcing is defined as selecting and working with two equivalent suppliers for a certain material. Agreements as to how detection of defects is resolved and as to the terms of payment made. Canvassing is the main sourcing strategy used by the company. Fiscal counting of inventory is performed by the company every end of the first year. Small discrepancies of 5% are often disregarded as shown by past data. First-In-First-Out policy is the system employed in the cost flow method used for operational disbursement of inventories. The storage of raw materials is essentially based on space availability and utilization. The materials are also arranged based on the nature of the items. The company has a made-to-order operation wherein they only buy the required or lacking raw materials when a production order is scheduled and then the current inventory levels are determined. Bin cards, which are index cards, are used in the receiving of goods and ordered raw materials. Two closed vans with pushcarts are available for transportation operations perusal. These are used for the transportation of finished goods within Luzon. For finished goods that need to be shipped, forwarders are contacted. The company has not provided a location for customer service center and does not intend to have one. According to the president, their current location and facilities are enough to accommodate all their customers. The persons in charge of customer service are the administrative officers of the company. They are in charge of entertaining queries and accepting complaints. The group made use of streamline analysis in identifying the problem areas in the company. Based on the streamline diagnostic chart, the three emerging main problems are the following: limited purchasing strategies, supplier inability to deliver on time, and ineffective warehousing and inventory policy. Alternatives were generated and evaluated using cost-benefit analysis. The alternatives are as follows (1) improved inventory and warehousing strategies plus warehouse expansion, (2) use of third party warehousing, and (3) adopting co-managed inventory system. It was found that the first alternative is the best action to take in order to address the problems identified. The recommendation of the group is to improve inventory and warehousing strategies and to expand the company warehouse. Included in the recommendation are the following: adopting an appropriate forecasting technique, use of the fixed-order quantity model for the determination of the reorder points and the optimum amounts of order, and rearrangement of storage areas with priority to maximization of space utilization and availability. The group also suggested that the current facility of the company might need an expansion. Only one warehouse is enough since there has been no problem regarding location and product distribution. The company should establish clear and written procedures for receiving, shipping, and material handling operations. Implementing strategies include establishment of a changeover date, budget development, training of personnel involved, establishment of a good records management program, production of manuals or documents of standard operating procedures, preparation for moving day, determination of the optimum location of inventory storage areas, and creation of a mechanism to apply the forecasting technique selected by the company.